ABORSI PADA KASUS PEMERKOSAAN ANAK PERSPEKTIF UNDANG-UNDANG NOMOR 17 TAHUN 2023 - Raden Mas Airell Jordan Hidayat; Rospita Adelina Siregar (Honeste Vivere, 2026)
One of the most common violations of law and human rights today is rape. The legalization of abortion in the Health Law is essentially based on a derivative concept aimed at protecting women's reproductive health rights and dignity. Although there are laws that allow abortion under certain conditions—such as in cases where pregnancy is unintended and the woman is a victim of rape, often involving minors—abortion practices in society are still widely regarded as a violation of human rights, as the fetus is also considered to have the right to life. The research problem addressed in this study is: how does Law Number 17 of 2023 on Health regulate abortion in cases of child rape? Abortion performed by child victims may be legally justified based on Article 60 of Law Number 17 of 2023 on Health, although the law does not clearly specify a minimum age limit for undergoing an abortion. While abortion is legally permitted, it must be carried out in accordance with the provisions set forth in existing legislation.